A CASE OF PANHYPOPHYSITIS THAT MYSTERIOUSLY DISAPPEARED - Ramli, Fathiyah; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Hamzah , Wan Mohd Hafez Wan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Panhypophysitis is a rare inflammatory condition that affects the entire pituitary gland, predominantly affecting women of reproductive age. Presentation is often vague, complicating diagnosis and management. We report a possible lymphocytic panhypophysitis that resolved with corticosteroids given for another indication. CASE A 31-year-old Indonesian female with an underlying diabetes mellitus presented with lethargy, polyuria, and polydipsia for four months. Previously, she had 3 uneventful deliveries. She was admitted for hyperosmolar hyperglycaemic state and noted to have persistent hypernatraemia with urine output of 3-4 litres daily. Further investigations were consistent with central diabetes insipidus (urine osmolality: 74 mOsm/kg, serum osmolality: 337 mOsm/kg, serum sodium: 152mmol/), and responded to desmopressin. Anterior pituitary hormones showed central hypothyroidism (TSH 0.14 mIU/L, T4: 7.8 pmol/L), hypogonadothrophic hypogonadism (LH 0.9 IU/L, FSH 3.4 IU/L, estradiol 108 pmol/L) and secondary hypocortisolism (18 nmol/L). She received hormonal replacement. MRI pituitary reported a homogeneously-enhancing pituitary lesion extending into the suprasellar region, which abuts the chiasm, with loss of the posterior pituitary bright spot, concerning for panhypophysitis. Further investigations for secondary hypophysitis were negative. Later, she was admitted for bilateral lower limb weakness and sensory deficit, with initial concern of transverse myelitis, and she was started on IV methylprednisolone for 3 days. Subsequent MRI spine revealed no spinal cord pathology, and the diagnosis was revised to diabetic neuropathy. Follow-up MRI pituitary after 9 months showed complete resolution of the pituitary lesion and normalization of the infundibulum. Her clinical condition improved, and the desmopressin dosage was reduced. CONCLUSION The resolution of the pituitary lesion after high-dose cortico- steroids in our case supports a diagnosis of lymphocytic hypophysitis, the most common form of hypophysitis. High-dose steroids likely halted the inflammatory process, resulting in structural and functional recovery. A trial of medical therapy may be considered in similar cases before opting for surgical intervention.